Rapid and sensitive detection of nitroaromatic explosives by using new 3D lanthanide phosphonates. Issue 5 (18th January 2017) - Fu, Ruibiao; Hu, Shengmin; Wu, Xintao
Abstract : A terbium phosphonate with its bright green emission, facile synthesis, and low usage can sense nitroaromatic explosives at the ppb scale rapidly. Abstract : A luminescent terbium phosphonate metal–organic framework (MOF) exhibits a remarkable capability to rapidly detect traces of nitroaromatic explosives (as low as 66 ppb) through luminescence quenching. Its sensitivity, fast response, facile synthesis, low usage (less than 0.1 mg), cheapness, and good stability make it one of the most powerful nitroaromatic explosive sensors known.